THE EFFECTIVENESS OF SMART BOX MEDIA WITH PROBLEM-BASED LEARNING MODELS IN IMPROVING SCIENCE LEARNING OUTCOMES OF GRADE IV STUDENTS IN PUBLIC ELEMENTARY SCHOOLS - Talitha Salsabila Azalea; Barokah Isdaryanti (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2026)
This study aims to assess how well the Smart Box tool works to determine the effectiveness of Smart Box media in improving science learning outcomes for 4th grade students in elementary schools. The approach applied is an experimental study using an Unequal Control Group design, consisting of two groups: an experimental group consisting of 27 students and a control group consisting of 28 students. Information was collected through learning outcome assessments using pre-tests and post-tests. The average initial score of the experimental group was 65.30. After using Smart Box Media, the average experimental group increased to 89.00. While the average Pretest of the control class was 64.07, increasing to 70.36. These findings indicate that by using Smart Box media, learning outcomes are higher and can make students active, collaborative and increase understanding of the material that has been delivered by the teacher. This study concludes that Smart Box media is effective for improving science learning outcomes in elementary schools.